An agile assistant robot integrating operation and rolling locomotion. Issue 1 (16th January 2017) - Li, Yezhuo; Yao, Yan-An; Cheng, Junlin; Tian, Yaobin; Liu, Ran
Abstract : Purpose: The purpose of this paper is to propose an agile assistant robot to be used as a mobile partner with two rotational motions and one translational motion. This robot possesses the rolling function and three operating abilities to assistant human beings in the industrial environment. Design/methodology/approach: The main body of the robot is a typical 4-RSR (where R denotes a revolute joint and S denotes a spherical joint) parallel mechanism. The mechanism can reach any position on the ground by two rolling modes (the equivalent Watt linkage rolling mode and the equivalent 6R linkage rolling mode), and the robot can work as a spotlight or a worktable in operating modes at the target location. The mobility, rolling modes, operating modes and kinematics are analyzed. Findings: Based on the results of kinematics of this assistant robot, the upper platform of the 4-RSR rolling mechanism has two rotational motions and one translational motion which can be used in the industry. The proposed concept is verified by experiments on a physical prototype. Practical implications: This paper also discusses the application to industrial cases where cooperation between workers and robots is required. Originality/value: The work presented in this paper is a novel exploration to apply parallel mechanisms to the field of assistant rolling robots. It is also a new attempt to use the rolling mechanism in the field of mobile operating robots for industry tasks.